Luminal Pharmacokinetics, Pharmacodynamics, and Acceptability of Four Rectal Microbicide Vehicle Candidates in the Distal Colon - Leyva Hurtado, Francisco José (2012)
Due to the risk of HIV infection, a rectal microbicide (RM) is needed as a prophylactic. This clinical study evaluated the pharmacokinetics luminal and pharmacodynamics of four candidate formulations as MR vehicles. Eight men participated in this randomized, partially blinded comparative study. Formulations aqueous fluid (AF), aqueous gel (AG), lipid fluid (LF) and lipid gel (LG), were mixed with diethylenetriaminepentaacetic acid labeled with Technetium-99m and administered intrarectically. One hour later, colon biopsies and brushings were obtained using sigmoidoscopy. SPEC/CT images were obtained at 2, 4, and 24 hours. Colonic distribution was described using concentration-distance (Dmax) parameters. Colonic histology did not find differences in epithelial denudation. Luminal concentrations of AG and LF and tissue concentrations of LF showed a significant decrease (p<0.05) compared to AF. The permeability of lipid products was significantly higher than in aqueous products (p<0.05). Colonic distribution showed a significantly shorter Dmax at 4-hours than at 2-hours (p=0.014). LF had a significantly shorter Dmax than AF (p=0.009). This study has shown that AF, AG and LG formulations do not damage the colonic epithelium. All formulations showed a decrease in colonic distribution over time. The lipid formulations showed greater permeability than the aqueous ones.